Pengaruh Akuntansi Keberlanjutan Pada Industri Perbankan (Studi Kasus Bank Mandiri) - Dwi Urip Wardoyo; Nabilah Milzam; Risqa Putri Ramadhani; Ruth Damayanti Hariyanto (Jurnal Ilmiah Wahana Pendidikan, 2023)
Sustainability accounting is very important for a company because it can help the company in operational impacts related to the environment and surrounding communities, that is why sustainability accounting has a big impact, especially for the banking industry. This study aims to look for influences related to the implementation of sustainability accounting in the banking industry. Then, Bank Mandiri is an example of a banking industry that implements sustainability accounting. The method used in this study is a qualitative perspective or paradigm approach and a causality approach. The results of the study can be concluded that sustainability accounting influences the operational activities of Bank Mandiri, so it is suggested that Bank Mandiri continues to strive to improve the company's environmental performance.